Suicide in Inmates in Nazis and Soviet Concentration Camps: Historical Overview and Critique - López-Muñoz, Francisco; Cuerda-Galindo, Esther (Frontiers in Psychiatry, 2016)
Living conditions in concentration camps were harsh and often inhumane, leading many prisoners to commit suicide. We have reviewed this topic in Nazi concentration camps (KL), Soviet special camps, and gulags, providing some preliminary data for our research. Data show that the incidence of suicide in Nazi KL could be up to 30 times higher than the general population and was also much higher than in Soviet special camps (maybe due to more favorable conditions for prisoners and the abolishment of death penalty), while available data on Soviet gulags are contradictory. However, data interpretation is very controversial, because, for example, the Nazi KL authorities used to cover-up the murder victims as suicides. Most of the suicides were committed in the first years of imprisonment, and the method of suicide most commonly used was hanging, although other methods included cutting blood vessels, poisoning, contact with electrified wire, or starvation. It is possible to differentiate two behaviors when committing suicide; impulsive behavior (contact with electrified barbed wire fences) or premeditated suicide (hanging up or through poison). In Soviet special camps, possible motives for suicides could include feelings of guilt for crimes committed, fear of punishment, and a misguided understanding of honor on the eve of criminal trials. Self-destructive behaviors, such as self-mutilation in gulag camps or prisoners who let themselves die, have been widely reported. Committing suicide in concentration camps was a common practice, although precise data may be impossible to obtain.